2022
DOI: 10.1371/journal.pone.0265561
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of knowledge, attitudes and perceptions towards malaria prevention among people living in rural upper river valleys of Nepal

Abstract: Background Nepal has made significant progress in decreasing the number of malaria cases over the last two decades. Prevention and timely management of malaria are critical for the National Malaria Program in its quest for elimination. The study aimed to explore the knowledge, attitudes and behaviour towards malaria prevention and treatment among people living in rural villages of Khatyad Rural Municipality in Nepal. Methods This qualitative study collected information through virtual in-depth interviews (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Whereas this study was not necessarily about drowning by children, the findings point to the need to focus on child-specific policy and programme interventions such as the inclusion of swimming lessons and heightened supervision of swimming pools and other water bodies to minimize cases of children drowning in Uganda. These findings are consistent with those of a related survey-based study in South Africa which showed that 52.2% of fatal drowning incidents occurred on weekdays and 47.8% occurred on weekends and public holidays [ 21 ]. The same study further provided a set of developmental characteristics and multiple contextual factors which put children living in low-income countries such as Uganda at increased risk for drowning.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…Whereas this study was not necessarily about drowning by children, the findings point to the need to focus on child-specific policy and programme interventions such as the inclusion of swimming lessons and heightened supervision of swimming pools and other water bodies to minimize cases of children drowning in Uganda. These findings are consistent with those of a related survey-based study in South Africa which showed that 52.2% of fatal drowning incidents occurred on weekdays and 47.8% occurred on weekends and public holidays [ 21 ]. The same study further provided a set of developmental characteristics and multiple contextual factors which put children living in low-income countries such as Uganda at increased risk for drowning.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…The private sector plays an important role in the delivery of HS interventions for the management of malaria in multiple countries98 as public health facilities in low-income and middle-income countries often have limited or no medical supplies, including essential malaria test kits 69. The limited opening hours of outpatient services at public facilities, costs incurred to travel to a public health facility and the proximity of a private sector provider to the community can all influence the choice of healthcare provider 109–111. In such conditions, private sector providers can become the preferred option for malaria control by providing HS in communities, especially for children and older people, as they can bridge the gaps in the existing healthcare system,109 111 112 and minimise self-treatment rates 55.…”
Section: Discussionmentioning
confidence: 99%
“…Like many other studies it is recommended in the present study to have ongoing continuous knowledge update of all the cadres of HCPs in the management and prevention of not only malaria but also all the major vectors borne diseases. [7][8][9][10]…”
Section: Discussionmentioning
confidence: 99%